Improving Lecturers’ Performance through Effective Learning at Department of Islamic Education at Faculty of Islamic Education and Teacher Training IAIN IB Padang - Zulvia Trinova (AT-TA'LIM, 2015)
The aim of this study is to describe the work situation variables, achievement motivation on the performance of Islamic education (PAI) lecturer in creating effective learning in the Department of PAI. This study is a combination of quantitative  and qualitative methodss  (mixed methods)  obtained from observation, questionnaire, interviews, and documentation. The data were analyzed through  statistics. Qualitative data were analyzed  by using data reduction, categorization, and data verification  and conclusions. The working athmosphere contributes 48.7%  to the influence on the lecturer  performance  work and the motivation contributes  43.0% to the impact on the lecturer performance. Work situation and achievement motivation respectively affect the work performance of 58.3%. Learning approach used is expository approach, the inquiry, and emotional approach. It was also  used PAKEM approach and an approach that is Andragogy. The learning method applied in this research is multi method in the form of active active learning. PAI lecturers used printed media, dicussion paper, and  electronic media. Keywords: Effective learning,  PAI, performance.Copyright © 2015 by Al-Ta'lim All right reserved